Global Warming Amplifies Nitrogen Over Phosphorus Limitation in Aquatic Ecosystems: A Multi‐Trophic Meta‐Analysis - Misha Zhong; Ping Xie; Yuhao Feng; Wenxuan Han; Enzai Du; Di Tian; Ruijing Ma; Yuwei Wang; Zengliang Jian; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; et al. (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) availability fundamentally regulate the structure and function of aquatic ecosystems. While global‐scale patterns of relative nutrient limitation have been increasingly documented, their responses to climate warming remain poorly quantified. To address this, we integrated a global meta‐analysis of nutrient enrichment experiments (spanning 510 sites and multiple trophic levels) with large‐scale datasets of water chemistry from 3403 lakes and 13,032 marine sites. Meta‐analysis showed that primary producers have the strongest responses to nutrient enrichment, especially NP co‐addition, with effects attenuating at higher trophic levels. Increasing temperature amplifies the response of primary producers to nutrient enrichment, but not for consumers, indicating that warming disrupts energy flow to higher trophic levels. Furthermore, relative N limitation of primary producers intensifies with increasing temperature and decreasing latitude in both freshwater and marine ecosystems. Global field observation of water chemistry supports such a pattern as water N:P mass ratios decrease with increasing temperature across lake and marine ecosystems. Our findings provide robust empirical evidence that the relative nutrient limitation of primary producers exhibits a strong latitudinal gradient and climate warming could fundamentally enhance nitrogen over phosphorus limitation in aquatic ecosystems, which have critical implications for ecosystem functioning and management in a warmer world.